What is the SKA-Low sensitivity for your favourite radio source?. (15th April 2022) - Sokolowski, M.; Tingay, S. J.; Davidson, D. B.; Wayth, R. B.; Ung, D.; Broderick, J.; Juswardy, B.; Kovaleva, M.; Macario, G.; Pupillo, G.; Sutinjo, A.
Abstract: The Square Kilometre Array (SKA) will be the largest radio astronomy observatory ever built, providing unprecedented sensitivity over a very broad frequency band from 50 MHz to 15.3 GHz. The SKA's low frequency component (SKA-Low), which will observe in the 50–350 MHz band, will be built at the Murchison Radio-astronomy Observatory (MRO) in Western Australia. It will consist of 512 stations each composed of 256 dual-polarised antennas, and the sensitivity of an individual station is pivotal to the performance of the entire SKA-Low telescope. The answer to the question in the title is, it depends. The sensitivity of a low frequency array, such as an SKA-Low station, depends strongly on the pointing direction of the digitally formed station beam and the local sidereal time (LST), and is different for the two orthogonal polarisations of the antennas. The accurate prediction of the SKA-Low sensitivity in an arbitrary direction in the sky is crucial for future observation planning. Here, we present a sensitivity calculator for the SKA-Low radio telescope, using a database of pre-computed sensitivity values for two realisations of an SKA-Low station architecture. One realisation uses the log-periodic antennas selected for SKA-Low. The second uses a known benchmark, in the form of the bowtie dipoles of the Murchison Widefield Array. Prototype stations of both types were deployed at the MRO in 2019, and since then have been collecting commissioning and verification data. These data were used to measure the sensitivity of the stations at several frequencies and over at least 24 h intervals, and were compared to the predictions described in this paper. The sensitivity values stored in the SQLite database were pre-computed for the X, Y, and Stokes I polarisations in 10 MHz frequency steps, $\scriptsize{1/2}$ hour LST intervals, and $5^°$ resolution in pointing directions. The database allows users to quickly and easily estimate the sensitivity of SKA-Low for arbitrary observing parameters (your favourite object) using interactive web-based or command line interfaces. The sensitivity can be calculated using publicly available web interface (http://sensitivity.skalow.link ) or a command line python package (https://github.com/marcinsokolowski/station_beam ), which can also be used to calculate the sensitivity for arbitrary pointing directions, frequencies, and times without interpolations.